Effects of extruded soybeans on CLA concentration in milk - A. Formigoni (Italian Journal of Animal Science, 2011)
Conjugated linoleic acids are geometric and positional isomers of the linoleic acid (Bessa et al., 2000). Recent studies on animal models demonstrated that these intermediates of rumen biohydrogenation may improve health by anticarcinogenic, antiatherogenic, antiobesity and antidiabetic effects and immune system enhancement (Bauman et al., 2001; Pariza et al., 2000; Belury 2002; Peterson et al., 2002). So aim of this work was to study the possibility to increase CLA milk content by the use of a natural source of polyunsaturated fatty acids as extruded soybeans........